2022
DOI: 10.3390/nu14142983
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Assessed Weight Change and All-Cause Mortality among Community-Dwelling Older People

Abstract: Later life changes in body weight may be associated with an increased risk of mortality in older adults. The objective of this study was to examine whether weight change over four years was associated with a 17-year mortality risk in older adults. Participants were 1664 community-dwelling adults aged ≥65 years in the longitudinal Enquete de Sante’ Psychologique-Risques, Incidence et Traitement (ESPRIT) study. Outcomes were all-cause mortality, cardiovascular disease (CVD) and cancer mortality. Weight change wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…Previous studies have reported an association between weight loss and subsequent mortality, but these studies included only a small number of older adults, typically with multiple comorbidities (eTable 14 in Supplement 1). Our study extends the previous observations by demonstrating a similar association among relatively healthy community-dwelling individuals aged 65 years or older. The results also showed that weight loss was more associated with mortality among men than women.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous studies have reported an association between weight loss and subsequent mortality, but these studies included only a small number of older adults, typically with multiple comorbidities (eTable 14 in Supplement 1). Our study extends the previous observations by demonstrating a similar association among relatively healthy community-dwelling individuals aged 65 years or older. The results also showed that weight loss was more associated with mortality among men than women.…”
Section: Discussionsupporting
confidence: 90%
“…By contrast, the Guangzhou Biobank study showed that self-reported weight loss was associated with higher CVD mortality and cancer mortality . These studies differed from the present cohort by including participants with various chronic diseases and not adjusting for or excluding individuals with a recent hospitalization . Our study showed that weight loss was associated with all-cause mortality and an increase in all major causes of death, including cancer and CVD in an initially healthy population.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations